Self-doped N, S porous carbon from semi-coking wastewater-based phenolic resin for supercapacitor electrodes - Yan, Long; Wang, Xianjie; Wang, Yufei; Li, Jian; Liu, Qianqian; Zhong, Xiang; Chang, Yuan; Li, Qingchao; Verma, Santosh Kumar (Frontiers in Chemistry, 2022)
Contamination of phenolic compounds has devastating effects on the environment. Therefore, its harmless treatment and recycling have received extensive attention. Herein, a novel method for preparing N-S doped phenolic resin (NSPR) from phenols, N and S groups in semi-coking wastewater, and formaldehyde are developed. The KOH is consequently incorporated into the NSPR through simultaneous carbonization and activation in a single step to produce porous carbon material (NSPC). The as-obtained NSPC exhibits a high specific capacitance of 182 F g-1 at 0.5 A g-1, a high energy density of 9.1 Wh kg-1 at a power density of 0.15 kW kg-1, and remarkable cycling stability in aqueous KOH electrolyte. This outstanding electrochemical performance is attributed to its ultrahigh specific surface area (SSA, 2523 m2 g-1), enormous total pore volume (Vt, 1.30 cm3 g-1), rational pore structure, and N-S heteroatom self-doping (0.76 at% N and 0.914 at% S), which ensures adequate charge storage, rapid electrolyte ion diffusion, and contributed pseudo-capacitance. This work not only provides a facile method for transforming phenolic wastewater into high-value products but also offers a cost-effective and high-performance porous carbon material for supercapacitors.